Corporate social responsibility and accountability: a new theoretical foundation for regulating CSR - Mallika Tamvada (International Journal of Corporate Social Responsibility, 2020)
Abstract The absence of consensus on what should constitute Corporate Social Responsibility has inhibited consistent CSR legislation around the world. This paper poses a fundamental question on what should constitute CSR and what should be the nature of CSR regulation? By constructing the boundaries of CSR, the paper offers scope for consistently developing CSR regulation around the world. It construes CSR as consisting of business relation and impact relation, and demonstrates that these are intertwined with legal responsibilities of business and, consequentially, with accountability. It accomplishes this by establishing the obligatory nature of responsibilities using the lens of ethical and legal jurisprudence. This new approach towards CSR recasts it as an obligatory responsibility that is linked to accountability. Furthermore, the framework provides a foundation for consistent development of CSR regulation across different countries that can lead to effective discharge of corporates’ social responsibilities.